Kiai sebagai Kekuatan Politik dalam Pemilihan Presiden 2019 di Jawa Timur - Mukari, Mukari; Muharam, Moch Mubarok; Fithriyyah, Mustiqowati Ummul (State Islamic Institute of Kudus (IAIN Kudus), 2022)
This study aims to analyze the political power of the kiai in the 2019 Presidential Election in East Java Province, Indonesia. The research method we use is a qualitative method with a case study type. Data collection techniques were carried out through in-depth interviews to obtain primary data and literature review through books and journals. How the power and actions of kiai in the 2019 presidential election are the focus of this journal research. The theory of political elites from Vilvredo Pareto and Gaetano Mosca becomes the basis for the analysis of this journal. The results of this study see that the kiai have succeeded in winning the pair Joko Widodo (Jokowi) and Ma'ruf Amin in the 2019 presidential election and can minimize the existence of identity politics in East Java. This study concludes that this success is due to the existence of the kiai as an elite in society. With moral integrity, the depth of religious knowledge and concern for the problems that exist in society become a separate political force for the kiai.